(untitled) (Research, Society and Development, 2021)
Forensic dentistry is an area of forensic science charged with assisting justice primarily in cases of human identification. Identification techniques date back to 49 AD, and their use has been recorded throughout history. Bite mark analysis is a complex technique that carries with it many subjectivities, dividing opinions and generating much controversy. This article consists of a narrative literature review and discusses how the identification of bite marks is performed, highlighting its importance and limitations, also pointing out the role of the dentist. A search was conducted in the databases "PubMed", "Scielo" and "Lilacs" during the last 20 years using the descriptors in portuguese: “Mordida Humana”, “Odontologia Forense”, “Mordida" and in english: “Bite Human”, “Forensic dentistry” and “Bite”. These marks are mainly found in crimes of sexual abuse, murder, and child abandonment, where the offender uses his teeth as a weapon, leaving a mark on the victim’s skin or on objects left at the scene of the crime. Based on the principle that the dental arch is unique to each human being, a comparison is made between the mark left at the crime scene and the dentition of the suspect, which may incriminate the individual. Therefore, it is concluded that bite marks can be an important tool in solving crimes, provided that they are performed in a judicious manner, by qualified professionals and respecting their limitations.